COVID-19 Infodemic in Malaysia: A Reflection towards Improving the Regulatory Framework on Misinformation and Fake News (Kanun: Jurnal Undang-undang Malaysia, 2023)
The recent COVID-19 pandemic saw the rise of fake news and misinformation dissemination. Experts agree that this phenomenon is caused by the availability of an overabundance of information, also known as infodemic. This infodemic phenomenon has negatively affected the efforts of the authorities across the world to deal with the threat of the pandemic. In the meantime, while there is a fact-checking eco-system in Malaysia, it seems to fail to solve problems related to the infodemic effectively. The enforcement of existing laws has also been viewed as undemocratic and draconian instruments by its critics. What is more worrying is that the traditional legislation approach has been increasingly considered archaic and increasingly out of pace in catching up with the rapid development of technology. Therefore, a new approach is needed to regulate infodemic. Thus, the main objective of this paper is to re-examine the effectiveness of the fact-checking eco-system and legislation related to the existing infodemic regulation. This paper will also recommend new methods, including using technology, to regulate the infodemic in the future. This paper will also examine other countries’ approaches in facing infodemic challenges. Therefore, to achieve the research objective stated above, this paper uses qualitative research methodology to formulate its findings, primarily through the textual analysis of several related legislations and also of available secondary sources, such as academic manuscripts, textbooks, online resources and other relevant sources.Keywords: Infodemic, Malaysia 5.0, COVID-19, misinformation, fake news, freedom of speechFull text: PDF